2002
DOI: 10.1093/jnci/94.20.1555
|View full text |Cite
|
Sign up to set email alerts
|

Tumors of the Nervous System and Pituitary Gland Associated With Atomic Bomb Radiation Exposure

Abstract: A statistically significant dose response was observed for all nervous system tumors combined and for schwannoma considered separately, indicating that exposure to even moderate doses (i.e., <1 Sv) of radiation is associated with an elevated incidence of nervous system tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
165
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(177 citation statements)
references
References 37 publications
9
165
0
3
Order By: Relevance
“…Four studies that have quantified the risk between IR and brain cancer have reported estimations that vary in terms of the magnitude of the risk per Gy. The Israeli tinea capitis study found an ERR per Gy of 1.98 (95% CI: 0.73 -4.69) for glioma after a mean dose to the brain of 1.5 Gy (range: 1.0 -6.0 Gy) (Sadetzki et al, 2005); a pooled analysis of two Swedish cohorts of infants who received radium treatment for haemangiomas (mean absorbed intracranial dose: 7 cGy; range: 0 -11.5 Gy) estimated the ERR per Gy for all brain tumours as 2.7 (95% CI: 1.0 -5.6) (Karlsson et al, 1998); a childhood cancer survivor study reported an ERR per Gy of 0.33 (95% CI: 0.07 -1.71) for glioma (Neglia et al, 2006) after radiation doses ranging from o1 Gy to 445 Gy; and the LSS found an ERR per Gy for glioma of 0.6 (95% CI: À0.2 to 2.0) (Preston et al, 2002b). Evidence of increasing risk of brain cancer with younger age at exposure has been provided by the first three aforementioned studies ( Figure 1B), whereas for the LSS, the risk was non-significantly higher for those exposed before age 20.…”
Section: Association Between Age At Exposure and Riskmentioning
confidence: 99%
“…Four studies that have quantified the risk between IR and brain cancer have reported estimations that vary in terms of the magnitude of the risk per Gy. The Israeli tinea capitis study found an ERR per Gy of 1.98 (95% CI: 0.73 -4.69) for glioma after a mean dose to the brain of 1.5 Gy (range: 1.0 -6.0 Gy) (Sadetzki et al, 2005); a pooled analysis of two Swedish cohorts of infants who received radium treatment for haemangiomas (mean absorbed intracranial dose: 7 cGy; range: 0 -11.5 Gy) estimated the ERR per Gy for all brain tumours as 2.7 (95% CI: 1.0 -5.6) (Karlsson et al, 1998); a childhood cancer survivor study reported an ERR per Gy of 0.33 (95% CI: 0.07 -1.71) for glioma (Neglia et al, 2006) after radiation doses ranging from o1 Gy to 445 Gy; and the LSS found an ERR per Gy for glioma of 0.6 (95% CI: À0.2 to 2.0) (Preston et al, 2002b). Evidence of increasing risk of brain cancer with younger age at exposure has been provided by the first three aforementioned studies ( Figure 1B), whereas for the LSS, the risk was non-significantly higher for those exposed before age 20.…”
Section: Association Between Age At Exposure and Riskmentioning
confidence: 99%
“…The incidence risk for nervous system tumors has been thoroughly evaluated by Preston et al [19] and Thompson et al [20]. Their evaluation on cancer incidence for atomic bomb survivors in the extended Life Span Study (LSS-E85), a cohort of about 80,000 people, give crude cancer incidence rates by dose and number of excess nervous system tumors.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Based on their data an absolute excess risk of about 0.002-0.003/Sv was derived. Schwannoma accounts for about 65%, meningioma about 20% and glioma plus astrocytoma about 10% of the expected excess cases [19]. The corresponding risk for pituitary tumors is about 10% of the risk for nervous system tumors [19].…”
Section: Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…First-degree relatives of patients with meningiomas have an increased risk of developing the disease, but the etiology remains largely unknown [3]. The only established environmental risk factor for meningiomas is ionizing radiation at both low and high doses [4][5][6][7]. There is a 2:1 female-to-male incidence ratio.…”
Section: Introductionmentioning
confidence: 99%